If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 + 6X + -1 = x + 2 Reorder the terms: 3 + -1 + 6X + 2x = x + 2 Combine like terms: 3 + -1 = 2 2 + 6X + 2x = x + 2 Reorder the terms: 2 + 6X + 2x = 2 + x Add '-2' to each side of the equation. 2 + 6X + -2 + 2x = 2 + -2 + x Reorder the terms: 2 + -2 + 6X + 2x = 2 + -2 + x Combine like terms: 2 + -2 = 0 0 + 6X + 2x = 2 + -2 + x 6X + 2x = 2 + -2 + x Combine like terms: 2 + -2 = 0 6X + 2x = 0 + x 6X + 2x = x Solving 6X + 2x = x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-2x' to each side of the equation. 6X + 2x + -2x = x + -2x Combine like terms: 2x + -2x = 0 6X + 0 = x + -2x 6X = x + -2x Combine like terms: x + -2x = -1x 6X = -1x Divide each side by '6'. X = -0.1666666667x Simplifying X = -0.1666666667x
| 27j-6=14j-7 | | 112=7w-168 | | 30m=22+80m | | 2x+24=-30+5x | | 21x+7=10x-1 | | 5(g-6)=48 | | 1.5x=1.23 | | r-9-(-42)=96 | | 9+4+10=56 | | 8(3x+40)=10 | | x^2-320=x-10 | | 3overx= | | 15=k-32 | | 3x+2-2=8-2 | | 18p-15=0 | | T(-3)=21 | | 2X+1=-x+2 | | -x+(-x)+(-x)+(-z)= | | 1.6k=5.75 | | 2x+12=3x-9 | | (x^2)+30x-2000=0 | | n-11=66 | | 11y+5=3(-5+2y) | | -.9x^2+45x=0 | | 8x-12-6x-1=1 | | v-52=29 | | 2(6x-10)=31-3(5-3x) | | -24x+-6+7x+9x-27=4 | | p-6=43 | | h*7=15 | | -3x^2+36x-33=0 | | a^2-10+9a=0 |